Effect Of Dual sEH/COX-2 Inhibition on Allergen-Induced Airway Inflammation - Dileepan, Mythili; Rastle-Simpson, Stephanie; Greenberg, Yana; Wijesinghe, Dayanjan S.; Kumar, Naren Gajenthra; Yang, Jun; Hwang, Sung Hee; Hammock, Bruce D.; Sriramarao, P.; Rao, Savita P. (Frontiers in Pharmacology, 2019)
Arachidonic acid metabolites resulting from the cyclooxygenase (COX), lipoxygenase, and cytochrome P450 oxidase enzymatic pathways play pro- and anti-inflammatory roles in allergic airway inflammation (AAI) and asthma. Expression of COX-2 and soluble epoxide hydrolase (sEH) are elevated in allergic airways and their enzymatic products (e.g., prostaglandins and diols of epoxyeicosatrienoic acids, respectively) have been shown to participate in the pathogenesis of AAI. Here, we evaluated the outcome of inhibiting the COX-2 and sEH enzymatic pathways with a novel dual inhibitor, PTUPB, in A. alternata-induced AAI. Allergen-challenged mice were administered with 10 or 30 mg/kg of PTUPB, celecoxib (selective COX-2 inhibitor), t-TUCB (selective sEH inhibitor) or vehicle daily by gavage and evaluated for various features of AAI. PTUPB and t-TUCB at 30 mg/kg, but not celecoxib, inhibited eosinophilic infiltration and significantly increased levels of anti-inflammatory EETs in the lung tissue of allergen-challenged mice. t-TUCB significantly inhibited allergen-induced IL-4 and IL-13, while a less pronounced reduction was noted with PTUPB and celecoxib. Additionally, t-TUCB markedly inhibited eotaxin-2, an eosinophil-specific chemokine, which was only marginally reduced by PTUPB and remained elevated in celecoxib-treated mice. PTUPB or t-TUCB administration reversed allergen-induced reduction in levels of various lipid mediators in the lungs, with only a minimal effect noted with celecoxib. Despite the anti-inflammatory effects, PTUPB or t-TUCB did not reduce allergen-induced airway hyperresponsiveness (AHR). However, development of structural changes in the allergic airways, such as mucus hypersecretion and smooth muscle hypertrophy, was significantly inhibited by both inhibitors. Celecoxib, on the other hand, inhibited only airway smooth muscle hypertrophy, but not mucus hypersecretion. In conclusion, dual inhibition of COX-2 and sEH offers no additional advantage relative to sEH inhibition alone in attenuating various features associated with A. alternata-induced AAI, while COX-2 inhibition exerts only moderate or no effect on several of these features. Dual sEH/COX-2 inhibition may be useful in treating conditions where eosinophilic inflammation co-exists with pain-associated inflammation.